A Novel Locus for Autosomal Recessive Retinitis Pigmentosa in a Consanguineous Pakistani Family Maps to Chromosome 2p - NAZ, SHAGUFTA (2010)
OBJECTIVE: To identify a disease locus for autosomal recessive retinitis pigmentosa in a consanguineous Pakistani family. DESIGN: Prospective linkage study. METHODS: Blood samples were collected and genomic DNA was extracted. A genome-wide scan was performed using 382 polymorphic microsatellite markers on genomic DNA from 4 affected and 5 unaffected family members, and logarithm of odds scores were calculated. RESULTS: A maximum 2-point logarithm of odds score of 3.14 at θ = 0 was obtained for marker D2S165 during the genome-wide scan. Fine mapping markers identified a 20.92-cM (19.98-Mb) interval flanked by D2S149 and D2S367 that cosegregates with the disease phenotype. Haplotype analyses further refined the critical interval, distal to D2S220 in a 12.31-cM (13.35-Mb) region that does not harbor any genes that previously have been associated with retinitis pigmentosa. CONCLUSIONS: Linkage analysis identified a new locus for autosomal recessive retinitis pigmentosa that maps to chromosome 2p22.3-p24.1 in a consanguineous Pakistani family.